Determinan Underpricing dengan Reputasi Penjamin Emisi Sebagai Moderasi dari Perspektif Perusahaan - Oktananda, M. Reza; Gantyowati, Evi (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
This study aims to provide empirical evidence regarding the factors that influence underpricing. The analysis technique uses multiple linear regression and MRA (Moderate Regression Analysis) analyses. The population in this study are companies that conduct IPOs on the Indonesia Stock Exchange. This study used purposive sampling and obtained 116 samples from 164 companies that completed IPOs in 2020 - 2022. The results showed that auditor reputation hurts underpricing, and the debt-equity ratio positively affects underpricing. In contrast, earnings per share and company age do not affect underpricing. The results of moderation testing show that underwriter reputation weakens auditor reputation and debt-equity ratio on underpricing, and underwriter reputation cannot moderate earnings per share and company age on underpricing.